Dynamics performance of the wind-power supply chain with transmission capacity constraints - Milton M. Herrera; Mauricio Uriona; Isaac Dyner (Institute of Advanced Engineering and Science, 2020)
Previous studies have shown that poor performance of energy supply chains arises from incorrectly interpret feedback information and time delays between decisions and actions in energy policy. This paper assesses alternatives to improve performance of wind-power supply chain with transmission constraints that contribute to enhance response capacity of the wind industry to changes of energy policy. In order to test these alternatives, this paper used a simulation model with system dynamics (SD), taking as case study Brazil. The simulation model represents the main time lags and fluctuations that exist in the wind-power supply chain. Four simulation scenarios were proposed to evaluate changes in auction-based policy in wind industry of Brazil. The results are related to operational capacity, inventory levels and response capacity. This paper provides an analysis of different scenarios that contribute with synchronization of auctions policy, including transmission capacity constraints.